1996
DOI: 10.1002/j.1875-9114.1996.tb03639.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine Neurotoxicity

Manfred Hauben

Abstract: A comprehensive search of the published literature was undertaken to identify reports providing patient‐specific data relating to adverse neurologic events with cyclosporine. References cited in the articles identified by the search were manually reviewed to ensure that articles were pertinent. Studies and case reports on cyclosporine neurotoxicity in which individualized patient data were provided were included for review and analysis. Information pertaining to all aspects of cyclosporine neurotoxicity, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Cyclosporine-induced neurotoxicity is a well-known side effect and, in particular, can induce psychosis. [61][62][63][64][65] Everolimus, also an immunosuppressant, is a drug that acts on the mechanistic target of rapamycin and that affects the growth of neural stem cells. 66 A case study has been reported in which everolimus also induced psychosis, 67 but in a previous study, the use of everolimus in children and adolescents with tuberous sclerosis resulted in a decrease in prepulse inhibition, an indicator of psychosis and sensorimotor gating.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine-induced neurotoxicity is a well-known side effect and, in particular, can induce psychosis. [61][62][63][64][65] Everolimus, also an immunosuppressant, is a drug that acts on the mechanistic target of rapamycin and that affects the growth of neural stem cells. 66 A case study has been reported in which everolimus also induced psychosis, 67 but in a previous study, the use of everolimus in children and adolescents with tuberous sclerosis resulted in a decrease in prepulse inhibition, an indicator of psychosis and sensorimotor gating.…”
Section: Discussionmentioning
confidence: 99%